Effective utilisation of ICT is the key to business success: case study of SMEs in Zimbabwe - Ruvinga, Caroline; Zhou, Munyaradzi (IOSR Journal of Computer Engineering, 2019)
The focus of this paper is to analyse the utilisation of information communication technology (ICT) among small and medium enterprises (SMEs) in Zimbabwe, as one of the major factors contributing to their limited growth. The data was collected using interviews, questionnaires and observations. The findings revealed that most SMEs have and are still increasingly acquiring state of the art information communication technologies but are not fully utilising the technology which has a negative impact on profit margins, market share and overall business effectiveness. The research paper recommends intensive training programs and workshops for SME owners on effective utilisation of ICT for them to experience business growth and success. The findings avail valuable information to both the Zimbabwean SME community and the entire business community in the country in terms of development of economy and creation of employment opportunities.